Students' Mathematical Critical Thinking Ability in Group Algebra Structure Course during the Covid-19 Pandemic - Riayuliatun, Evi; Sutarni, Sri (Universitas Muhammadiyah Surakarta, 2021)
Critical thinking skills are very important things that students must have during online learning. Critical thinking skills are useful for solving specific problems and being able to develop in a better direction. The purpose of this study is to analyze students' mathematical critical thinking skills in solving problems in the Group Algebraic Structure course during the Covid-19 Pandemic. The research method used in this research is descriptive qualitative research using written tests and interviews. From the results of the study, it was found that students with very high critical thinking levels were 20%, high critical thinking levels were 50%, moderate critical thinking levels were 23.33%, low critical thinking levels were 3.33% and very low critical thinking levels were 3.33%. Furthermore, from the results of the written test, 5 subjects were taken based on each indicator of mathematical critical thinking skills to be confirmed through interviews. From each student who has very high, high, medium, low and very low mathematical critical thinking skills, students have different achievements from each indicator.